HUBUNGAN ANTARA PENGETAHUAN, SIKAP, SOSIAL EKONOMI, DAN PENYEDIAAN JAMBAN KELUARGA DENGAN KEBIASAAN BUANG AIR BESAR SEMBARANGAN DI DESA RASAU JAYA 2 - Abrori Abrori (Jurnal Buletin Al-Ribaath, 2016)
One village is one of the villages in the subdistrict Rasau Jaya 2  Kubu Raya based on result from health districts Kubu Raya only 61% Healthy of home, latrine coverage in the district Rasau Jaya 2 only 61,8% As for the behavior of defecation districts Rasau Jaya 2 59,09%, the impact on people's habits defecation in a polluted environment and the impact on human health, such as diarrhea, typhoid and cholera, and skin diseases, other effects such as loss of aesthetic value of the environment. This study aimed to determine the relationship between attitudes and knowledge economy and the provision of latrines special families with defecation habits in the sub-district Rasau Jaya 2 at Regency of Kubu Raya. This is a quantitative research study design "cross-sectional" .sample this study based on the number of existing homes The village Rasau 2 with coverage 5 village a sample of 106 respondents. Result bivariate analysis showed a be a relationship between knowledge (p-value: 0.008), attitude (p-value: 0.24), Economics (p-value: 0.24), and the provision of latrines (p-value: 0.006) the habit of defecation in the District Belitang Sekadau.Recommended to the health authorities to provide education hazard problem doing defecation habits.                                                                                                                               Keywords: knowledge, attitudes, economics, provision of household toilets, defecation, carelessly,